Molecular Docking Study of Mangosteen (Garcinia mangostana L.) Xanthone-Derived Isolates as Anti Androgen - Suhandi, Cecep; Fadhilah, Ersa; Silvia, Nurfianti; Atusholihah, Annisa; Prayoga, Randy Rassi; Megantara, Sandra; Muchtaridi, Muchtaridi (Indonesian Journal of Cancer Chemoprevention, 2021)
Androgen receptor (AR) is the member of steroid hormone receptor involved in the progression of prostate cancer growth due to receptor over-activation. On the other hand, mangosteen (Garcinia mangostana L.) as a medicinal plant contains xanthone-derived compounds which were known to have cytotoxic activity towards any types of human cancer cells. This research aims to determine xanthone-derived isolates potency from mangosteen as AR antagonists. The study was carried out through molecular docking assay utilizing AutoDock 4.2.6 using androgen receptor obtained from PDB ID 2AM9, testosterone as native ligand, and bicalutamide, flutamide, and nilutamide as reference. The results indicated that three isolates (1,3,7-trihydroxy-2,8-di-(3-methylbut-2-enyl)xanthone, mangostinone, and trapezifolixanthone) have the highest potency to be AR antagonist seen from the lower bond-free energy value than all of reference ligand. The lowest bond-free energy was provided by mangostinone with a ΔG value of -10.05 kcal/mol. However, the highest difference of residual amino acids interaction with testosterone and similar interaction with bicalutamide was provided by 1,3,7-trihydroxy-2,8-di-(3-methylbut-2-enyl)xanthone, with five different amino acids with testosterone and nine similar amino acids with bicalutamide, respectively. Interestingly, 1,3,7-trihydroxy-2,8-di-(3-methylbut-2-enyl)xanthone has similar hydrogen bond with the key residue amino acids of AR (705-Asn and 711-Gln) which indicates probably partial agonist activity while mangostinone has the highest amount of hydrogen bond in the absence of hydrogen bond towards key residual amino acids of AR. The results concluded that three specific derived-xanthone compounds were predicted to have activity as AR antagonists.Keywords: Prostate cancer, Androgen receptor, Mangosteen, Xanthone, Molecular docking.